(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The function ofeducation is to provide opportunities for each student to reach his/her fullpotential in the areas of educational, vocational, social, and emotionaldevelopment. The school leader must ensure that guidance is an integral part ofeducation and that it is centered directly on this function. The presentinvestigation was directed towards the identification of Counselling needs ofthe secondary school students for this, a Counselling Needs inventory wasconstructed by the investigator. Results of the analysis indicate thatsecondary school students have strong Counselling needs, as perceived by theirteachers.